Protein quality malnutrition - Manary, Mark J.; Wegner, Donna R.; Maleta, Kenneth (Frontiers in Nutrition, 2024)
Protein quality refers to the evaluation of a food or a diet based on its amino acid composition, protein digestibility, and protein bioavailability. When these parameters are specified, either through direct measurement or estimation, the amino acids provided by the diet are compared to those required by a healthy individual, and based on this comparison, an adequacy ratio or score is assigned. Two widely used protein quality scoring systems are the protein digestibility-corrected amino acid score (PDCAAS) and the digestible indispensable amino acid score (DIAAS), neither of which account for the dietary source of the protein. In malnourished children, metabolic adaptations reduce the endogenous availability of amino acids and increase the demand for protein synthesis. These increased amino acid requirements are primarily driven by the presence of acute infection and the need for tissue accretion. This review examines two large clinical feeding trials involving moderately malnourished children, where dietary protein quality was carefully measured. The finding s suggest that protein quality scores alone do not reliably predict weight gain or recovery in these children and that consuming milk protein provides distinct advantages over vegetable-based proteins.